(3GdJPcjQGJ hJQHjI GdeDefs ((3MSf Hf eMeO Hf CMeO Hf MSf Hf MGJe Hf Ydi Hf LGHQ s)
(3ChdgG (B:s
(3GdMeO ddg Ydi JYdjeg gPg aUhd ef GdehGYX GdaUd GdChd CjgG GdSGcf Edi eScfg s
(3BNQgG (B:s
(3hCdMbfG HGdeJbjf hCdHSfG NdY GdEjeGf hGdjbjf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs